Effects of tocotrienol supplementation on platelet aggregation in subjects with metabolic syndrome - Gan, Yee Lin (2014)
An occlusive thrombus in vasculature either in arterial or venous, is a pathological condition that predisposes to most cases of cardiovascular diseases (CVDs). As reported by World Health Organisation (WHO), CVDs were among the major cause of deaths for noncommunicable diseases. Prescription of antithrombotic agents (e.g.aspirin, clopidogrel and warfarin) is a standard treatment given to patients to reduce the risk of death from cardiovascular events. However, presence of side effects and inter-individual variability in response towards these antithrombotic agents may limit the prevention of cardiovascular events throughout the world including Malaysia. Tocotrienols are a group of vitamin E besides tocopherols. Previous animal studies showed significant inhibition of platelet aggregation and antithrombotic effect after tocotrienol administration, but results in human trials are controversial. Therefore,this study was designed to ascertain the effect of tocotrienol supplementation on platelet reactivity in subjects with metabolic syndrome (MetS), by taking into account that MetS subjects are associated with prothrombotic state due to higher platelet reactivity and blood coagulability. Thus, an initiation of antithrombotic therapy is important for them to prevent thrombotic events. In this connection, a randomised, double-blinded, crossover, and placebo-controlled human trial was conducted with a total of 31 MetS subjects (15 males and 16 females) completed the study. Subjects recruited received two interventions in a random order, separated by a 15-day washout period in between the interventions. During the intervention, subjects consumed palm mixed tocotrienols 200 mg or placebo twice daily for 14 days followed by a postprandial study day. Post-intervention results demonstrated that reactivity of arachidonic acid and adenosine 5’-diphosphate (ADP) signalling platelet aggregation was not significantly different (p > 0.05) between tocotrienol and placebo interventions. For the results in terms of postprandial change,tocotrienols also did not exert inhibitory effect (p > 0.05) on these platelet aggregation measurements compared to placebo. No significant differences (p > 0.05) were found on the degree of platelet activation induced by thrombin mimic peptide and haemostatic measures (plasma D-dimer, plasminogen activator inhibitor type 1 (PAI-1), fibrinogen and undercaroxylated osteocalcin (ucOC)) between tocotrienol and placebo interventions, both post-intervention and postprandial. Among the inflammatory measures including plasma soluble P-selectin (sP-selectin), plasma soluble E-selectin (sE-selectin), plasma soluble intracellular adhesion molecules 1 (sICAM-1), plasma soluble vascular cell adhesion molecules 1 (sVCAM-1) and serum high sensitivity C-reactive protein (hsCRP), the results showed that there were no significant differences (p > 0.05) between tocotrienol and placebo interventions, both post-intervention and postprandial except for plasma sICAM-1, in which tocotrienols significantly lowered (p < 0.05) the plasma sICAM-1 during postprandial. Post-intervention results also showed that brachial systolic blood pressure (SBP) and aortic pulse pressure were significantly lower (p < 0.05) in tocotrienol intervention compared to placebo intervention. In conclusion, this study demonstrated that 14 days of 400 mg tocotrienol supplementation did not exert antithrombotic effects on platelet aggregation induced by ADP and arachidonic acid, thrombin mimic peptide induced platelet activation, and haemostatic and inflammatory measures.